Relationship learning : a conduit to internationalisation - Bhatti, Waheed Akbar; Larimo, Jorma; Servais, Per (Elsevier, 2020)
Internationalization opportunities can emerge through inter-organizational sharing, yet research on why and how organizations learn through relationship interactions is underdeveloped. We explore how learning in supplier-customer relationships contributes to organizational offerings through the knowledge development process. We identify relationship learning as an organizational dynamic capability by thematic analysis of qualitative longitudinal data from large as well as small and medium-sized organizations. Our case study of organizations demonstrates that nurturing personal relationships and paying attention to customer communication is core in knowledge sharing. Customer input is valuable in solution offerings, strengthening mutual work, and growth in internationalization within an existing relationship or in new ones. The results endorse that the knowledge development processes and commitments transpire at both ends of the relationship. The findings provide practical managerial implications for ensuring the development of open and transparent communication conduits in relationships. The process of providing a solution that addresses customers' needs must begin with understanding their work, issues, and the intended jobs they will perform.
Keywords: dynamic capability; customer needs; opportunity; microfoundations; internationalization process; enterprises; learning organisation; knowledge management; learning; interaction; cooperation (general); organisations (systems); customers; business; information; fi=Kansainvälinen liiketoiminta|en=International Business|